Judicial interpretations on "error of law on the face of arbitration award" - Yap, Poy Yee (2010)
In making an arbitration award, the arbitrator must define it clearly, unambiguously Justly and enforceability. Once the award is made and published, is a final and binding document and enforceable as a judgment of the High Court. However, the award can still be challenged when an arbitrator had committed a clear error of law on the face of an award where a court can set aside or remit the award to the arbitrator for further consideration. There is no provision in both 1952 Act and 2005 Act to limit and no clear definition as to what exactly means by "error of law on the face of award". Thus, it does not provide guidelines for the losing party to decide whether the award is error on the face of it and should they challenge the arbitral award under this ground. Normally it is for the court to decide. Hence, this research intends to determine the judicial interpretations on "error of law on the face of arbitration award". This research was carried out mainly through documentary analysis of law journals and law reports. Results show that there are four judicial interpretations for "error of law on the face of award". The first interpretation is when the award not satisfies the essential features of a valid award. Second, appears by the award that the arbitrator has proceeded illegally for instance decided using evidence which the law was not admissible or using principles of construction which the law did not countenance. Next interpretation is the error must be such that it can be found in the award, or in a document actually incorporated with it. Lastly, there is an error of law on the face of award when there is found some legal proposition which is the basis of the award and which is erroneous. It is recommended that the four judicial interpretations should be included in the Arbitration Act so that it can be the guidelines for the party who wish to challenge the award under the ground of error of law on the face of award.